Pengaruh Transaksi Pihak Berelasi Terhadap Kompensasi Manajemen Pada Industri Keuangan Di Indonesia - Maria Yudith Yubellia Ageng Millenia Adhie; Supatmi Supatmi (Jurnal Riset Akuntansi dan Keuangan, 2022)
This study aims to prove the effect of related party transactions on management compensation. The research sample consists of 99 financial companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period with a total of 297 firm-years of observation. The analysis technique uses panel data regression analysis. The results of the study indicate that the more companies carry out related party transactions related to trade receivables and related party transactions related to liabilities other than trade payables, it is proven that the higher the compensation received by the company's board of directors and board of commissioners. However, related party transactions related to assets other than trade receivables and related party transactions related to liabilities related to trade payables proved to have a negative effect on the compensation received by the company's board of commissioners. The effect of tunneling related party transactions on the compensation of the board of directors and the board of commissioners was found to be greater than that of propping related party transactions.